Perovskite / crystalline silicon four-terminal laminated solar cell and preparation method and application thereof
By using translucent electrodes with dielectric/metal/die multi-layer structures and green ionic liquid spin coating technology in perovskite/crystalline silicon four-end stacked solar cells, the problem of high cost and low efficiency of silicon-based solar cells is solved. , realizes high-efficiency photoelectric conversion and low-cost production, and is suitable for large-scale commercial applications.
Patent Information
- Application Number
- CN202310705973.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
The existing silicon-based solar cells have high production cost and limited efficiency. Traditional metal oxide transparent electrodes have carrier absorption in the near-infrared light region, which reduces the efficiency of the photocell and is difficult to use as the top electrode of perovskite single junction battery. .
Using a multi-layer structure of dielectric/metal/dielectric (DMD) semi-transparent metal electrode, the embedded layer of transition metal Al is inserted before the Ag layer is grown to form a high-transparent and low-resistance electrode, replacing the traditional ITO electrode, combined with Green ionic liquid spin coating technology prepares wide bandgap perovskite layers to improve photoelectric conversion efficiency.
It significantly improves the energy conversion efficiency of perovskite/crystalline silicon four-end stacked solar cells, reduces the preparation cost, is suitable for large-scale commercial production, and improves the photoelectric performance and stability of the device.
Smart Images

Figure CN119156034A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optoelectronic materials and devices, and in particular relates to a perovskite / crystalline silicon four-terminal stacked solar cell and a preparation method and application thereof. Background Art
[0002] Solar energy is a renewable, clean energy source that is of great significance to the sustainable development of mankind. Solar cells can directly convert solar energy into electrical energy. Photoelectric conversion efficiency and preparation cost are key factors that determine their industrial application. At present, silicon-based solar cells are the mainstream of solar cells, occupying 90% of the photovoltaic market. The efficiency of silicon solar cells has reached 25.6%, close to the Shockley-Queisser limit efficiency (29.4%), but the preparation cost remains high. Therefore, it is necessary to develop a method that can improve the efficiency of cells while reducing the preparation cost of silicon-based solar cells. Any semiconductor material cannot fully absorb the widely distributed sunlight. Semiconductor materials with different band gaps can be used to construct stacked devices to achieve the absorption of photons of different energies. Therefore, wide-bandgap perovskite materials can be stacked on the top of silicon cells to form stacked cells, broaden the spectral response of the cells, maximize the use of solar energy, and improve the efficiency of solar cells. The current theoretical limit of silicon-based stacking is 42.5%, which shows great development potential. Among them, perovskite / crystalline silicon four-terminal stacked solar cells can not only flexibly select perovskites with different bandgap widths to distribute light absorption, but also do not require current matching between sub-cells, which is easier to achieve.
[0003] The top cell in the perovskite / crystalline silicon four-terminal stack requires a transparent top electrode, especially with high transmittance to infrared light, while the traditional metal oxide transparent electrode increases the preparation cost to a certain extent. In addition, in the perovskite / crystalline silicon four-terminal stack solar cell, indium tin oxide (ITO) is a commonly used TCO conductive glass, but due to the carrier absorption phenomenon of ITO in the near-infrared wavelength region, the transmission amount of light to the bottom cell is reduced, resulting in nearly 5% parasitic absorption, reducing the efficiency of the cell, and it is not suitable as the top electrode of the perovskite single-junction cell. Therefore, it is necessary to prepare a transparent electrode with both conductivity, low cost and transmittance comparable to ITO. Summary of the invention
[0004] In view of the above-mentioned shortcomings, the purpose of the present invention is to provide a perovskite / crystalline silicon four-terminal tandem solar cell and its preparation method and application. The present invention introduces a high-transmittance, low-square-resistance semi-transparent multilayer electrode structure instead of an ITO electrode into a perovskite / crystalline silicon four-terminal tandem solar cell, which not only reduces the cost but also greatly improves the energy conversion efficiency of the tandem cell.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions:
[0006] The present invention provides a perovskite / crystalline silicon four-terminal stacked solar cell, comprising a top cell and a bottom cell, wherein the top cell is a perovskite solar cell, and the bottom cell is a crystalline silicon cell; the top cell comprises a conductive substrate layer, a hole transport layer, a perovskite layer, an electron transport layer, a modification layer and a semi-transparent metal electrode layer which are stacked in sequence; the semi-transparent metal electrode layer is a multilayer structure formed by sequentially stacking medium 1 / Al / Ag / medium 2; both medium 1 and medium 2 are transparent materials.
[0007] The dielectric / metal / dielectric (DMD) multilayer structure is considered to be a potential substitute for ITO electrodes, with the bottom dielectric acting as a seed layer and the top dielectric acting as a protective layer to improve long-term stability. In this type of electrode, a thin metal film is sandwiched between two anti-reflection dielectric layers to produce high transparency. The inventors of the present application realized that Ag has the lowest resistivity among all metals and has the best optical properties in the visible and near-infrared spectral ranges, so Ag is selected as the metal film in the DMD structure, and a pre-buried layer of transition metal Al is inserted before the growth of the Ag layer to improve the initial growth mode of the Ag film so that it has a low permeation threshold thickness (the minimum thickness required to achieve permeation), thereby reducing the square resistance and improving the conductivity.
[0008] Preferably, the medium 1 is LiF or SnO2, and the medium 2 is MoO3 or SnO2.
[0009] Preferably, the thickness of the medium 1 layer is 2 nm, and the thickness of the medium 2 layer is 20 nm.
[0010] Preferably, in the semi-transparent metal electrode layer, the thickness of the Al layer is 1-2 nm, and the thickness of the Ag layer is 9-13 nm. Further preferably, the thickness of the Al layer is 1 nm, and the thickness of the Ag layer is 11 nm.
[0011] The present invention also provides a method for preparing the above-mentioned perovskite / crystalline silicon four-terminal stacked solar cell, comprising the following steps:
[0012] S1. Providing a conductive substrate;
[0013] S2. Preparing a hole transport layer on the conductive substrate;
[0014] S3. Preparing a perovskite layer on the hole transport layer;
[0015] S4. Preparing an electron transport layer on the perovskite layer;
[0016] S5. Vacuum evaporation of a modified layer on the electron transport layer;
[0017] S6. Vacuum-depositing medium 1, Al, Ag and medium 2 on the modified layer in sequence to form a semi-transparent metal electrode layer to prepare a perovskite solar cell;
[0018] S7. Cover the surface of the silicon cell with one side of the perovskite solar cell coated with a semi-transparent metal electrode layer to obtain the perovskite / crystalline silicon four-terminal stacked solar cell.
[0019] Preferably, in step S1, the conductive substrate is ITO conductive glass.
[0020] Preferably, in step S2, the hole transport layer is P3CT, and the preparation steps are: spin coating P3CT on the surface of the conductive substrate, the spin coating conditions are 3900-4100 rpm for 30-40s, and annealing at 100-105°C for 9-11min after spin coating.
[0021] Preferably, in step S3, the preparation method of the perovskite layer is: dissolving methylammonium iodide, methylammonium bromide and lead iodide in an ionic liquid at a molar ratio of 1: (1.5-1.53): (2.5-2.56) to obtain a precursor solution; using a heated spin coating technique to spin coat the precursor solution on the surface of the hole transport layer, and annealing to obtain the perovskite layer. Further preferably, the ionic liquid is a non-protonic ionic liquid, such as methylamine acetate, methylamine butyrate, methylamine formate, etc.
[0022] The wide bandgap perovskite layer of the present invention uses a green ionic liquid as a solvent, which improves the current situation that the perovskite / crystalline silicon four-terminal stacked device is based on organic solvents, making the preparation method more green and environmentally friendly, and is expected to be widely used in the field of organic optoelectronics.
[0023] Preferably, the substrate temperature of the heated spin coating technology is 50-100° C., the annealing temperature is 80-120° C., and the annealing time is 5-10 min.
[0024] Preferably, the electron transport layer in step S4 is PCBM, and the preparation steps are: spin coating the PCBM solution on the perovskite layer, the spin coating conditions are 900-1100 rpm for 50-60s, and then spin coating at 1900-2100 rpm for 2-3s.
[0025] Preferably, the modified layer in step S5 is C 60 , the thickness is 17 to 22 nm, more preferably 20 nm. 60 It can not only work together with PCBM to play the role of electron transport layer, but also passivate the defects on the surface of perovskite, effectively reduce non-radiative recombination between interfaces, and significantly improve the photoelectric conversion efficiency of the device.
[0026] In step S7 of the present invention, the form of covering the side of the perovskite solar cell coated with the semi-transparent metal electrode layer on the surface of the silicon cell is not limited, for example, it can be fixed in a snap-on manner, or connected and fixed with ultraviolet light curing glue.
[0027] The present invention also provides an application of the above-mentioned perovskite / crystalline silicon four-terminal stacked solar cell in the field of optoelectronics.
[0028] The beneficial effects of the present invention are:
[0029] The present invention utilizes a semi-transparent metal electrode with a multilayer structure of medium 1 / Al / Ag / medium 2 to replace the ITO electrode, which not only broadens the spectral response range of the perovskite / crystalline silicon stacked solar cell and improves the efficiency of the solar cell, but also reduces the preparation cost, is suitable for large-area preparation, and is conducive to commercial industrialization.
[0030] The present invention obtains a semi-transparent metal electrode with high transmittance, low square resistance and mechanical flexibility by adjusting the thickness of the seed layer Al and Ag in the medium 1 / Al / Ag / medium 2 multilayer structure, which is used to prepare a semi-transparent perovskite / crystalline silicon four-terminal stacked solar cell and can significantly improve the photoelectric performance of the device.
[0031] The present invention uses ionic liquid as a solvent for the perovskite component, thereby achieving the purpose of preparing a wide-bandgap perovskite film in the air, greatly improving the repeatability of perovskite preparation, improving the quality of the wide-bandgap perovskite film, and being safe and environmentally friendly, thus promoting the development of the photovoltaic industry to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0033] Figure 1 This is a schematic diagram of the structure of a perovskite / crystalline silicon four-terminal stacked solar cell provided by an embodiment of the present invention;
[0034] Figure 2 JV curves of the perovskite top cell, silicon bottom cell and ordinary silicon cell in the perovskite / crystalline silicon four-terminal tandem solar cell with semi-transparent multilayer electrodes prepared in Example 2;
[0035] Figure 3 The influence of different thicknesses of Ag layers on the sheet resistance of the multilayer electrode in Examples 1 to 3 of the present invention;
[0036] Figure 4 is the transmittance of the multilayer electrodes prepared in Examples 1 to 3 at different wavelengths. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The laboratory humidity conditions of the following examples were about 40% and the temperature was 25°C.
[0039] Example 1
[0040] This embodiment provides a perovskite / crystalline silicon four-terminal stacked solar cell with a semi-transparent multilayer electrode, such as Figure 1 As shown, it includes a top cell and a bottom cell, the top cell is a perovskite solar cell, and the bottom cell is a crystalline silicon cell; the top cell includes a conductive substrate layer, a hole transport layer, a perovskite layer, an electron transport layer, a modification layer and a semi-transparent metal electrode layer stacked in sequence; wherein the semi-transparent metal electrode layer is a multilayer structure formed by sequentially stacking LiF / Al / Ag / MoO3.
[0041] The preparation method thereof comprises the following steps:
[0042] (1) The etched ITO conductive glass was ultrasonically cleaned in ethanol, detergent solution, ultrapure water, and ethanol for 15 minutes each, and the clean ITO substrate was obtained after drying with nitrogen and stored in an electronic drying cabinet.
[0043] (2) The cleaned ITO substrate in step (1) was placed in a UV instrument for ultraviolet ozone treatment for 15 minutes. 20 μL of the P3CT solution was dropped onto the treated ITO substrate and spin-coated using a coating machine (4000 rpm, 30 seconds), and then the substrate with the P3CT spin-coated was placed on a hot plate at 100° C. for 10 minutes for annealing to form a hole transport layer.
[0044] (3) Dissolve 36.7 mg of methylamine iodide, 39.7 mg of methylamine bromide, and 272.7 mg of lead iodide in 1 mL of methylamine acetate (MAAc) ionic liquid solvent, and stir at 60°C for 6 hours until completely dissolved to prepare a perovskite precursor solution. Preheat the ITO substrate with a hole transport layer on the surface to 50-100°C. Set the spin coater to 4000 rpm and run for 20 seconds. Take 100 μL of the prepared perovskite precursor solution and drop it on the surface of the hole transport layer, spin coat it into a film, and then anneal it in air at 100°C for 5 minutes to form a perovskite film.
[0045] (4) Dissolve 15 mg of PCBM in 1 mL of chlorobenzene solution and stir at room temperature for 1 hour at a speed of 400 rpm to obtain a PCBM solution. Take 25 μL of the dissolved PCBM solution and drop it on the surface of the perovskite film. First, spin coat it at a speed of 1000 rpm for 60 seconds, and then spin coat it at a speed of 2000 rpm for 2 seconds to form an electron transport layer. The slow coating method first and then fast coating method ensures the uniformity of the electron transport layer.
[0046] (5) Vacuum evaporation method is used to evaporate the modification layer material C 60 First, a 1 nm thick C layer was evaporated at a rate of 0.1 Å / s. 60 Then, a 19 nm thick C layer was deposited at a rate of 0.5 Å / s. 60 , ensure C 60 Uniformly evaporated on the surface of the electron transport layer to form a total thickness of 20nm C 60 Modification layer.
[0047] (6) After steaming 60 Afterwards, the four materials LiF / Al / Ag / MoO3 were evaporated in sequence, among which LiF was evaporated at a rate of 0.5 angstroms / second for 2nm, Al was evaporated at a rate of 0.5 angstroms / second for 1nm, Ag was evaporated at a rate of 2 angstroms / second for 9nm, and MoO3 was evaporated at a rate of 1 angstrom / second for 20nm, completing the preparation of the semi-transparent perovskite solar device.
[0048] (7) Covering the prepared semi-transparent perovskite device with one side coated with a semi-transparent metal electrode layer on a silicon cell to obtain a perovskite / crystalline silicon four-terminal stacked solar cell.
[0049] Under standard test conditions (AM1.5G illumination), the energy conversion efficiency of the perovskite top cell prepared in this example was measured to be 14.73%, the open circuit voltage was 1.11V, and the short circuit current was 73.36mA / cm 2 , the filling factor is 73.36%.
[0050] Example 2
[0051] The perovskite / crystalline silicon four-terminal stacked solar cell was prepared by the same method as in Example 1, except that the vapor deposition thickness of Ag in step (6) was 11 nm.
[0052] Under standard test conditions (AM1.5G illumination), the photoelectric performance of the perovskite / crystalline silicon four-terminal stacked solar cell prepared in this example was tested, as shown in Table 1 and Figure 2As shown, it can be seen that the energy conversion efficiency of the silicon bottom cell is 2.75%, and the energy conversion efficiency of the perovskite top cell is 17.30%. Adding the efficiency of the silicon bottom cell to the efficiency of the perovskite top cell, the efficiency of the perovskite / crystalline silicon four-terminal stacked device is 20.05%, which is better than the efficiency of ordinary silicon solar cells (17.19%).
[0053] Table 1 Photovoltaic parameters of different cells
[0054]
[0055]
[0056] Example 3
[0057] The perovskite / crystalline silicon four-terminal stacked solar cell was prepared by the same method as in Example 1, except that the vapor deposition thickness of Ag in step (6) was 13 nm.
[0058] Under standard test conditions (AM1.5G illumination), in the perovskite / crystalline silicon four-terminal stacked solar cell prepared in this embodiment, the energy conversion efficiency of the perovskite top cell is 15.99%, the open circuit voltage is 1.13V, and the short circuit current is 18.54mA / cm 2 , the filling factor is 76.10%.
[0059] The square resistance of the semi-transparent multilayer electrodes prepared in Examples 1 to 3 was tested, and the results are shown in Table 2 and Figure 3 shown.
[0060] Table 2 Sheet resistance of semi-transparent multilayer electrodes with different Ag layer thicknesses
[0061] electrode D1 / Al / Ag(9nm) / D2 D1 / Al / Ag(11nm) / D2 D1 / Al / Ag(13nm) / D2 Square resistance (Ω / sq) 26.1 15.7 14.7
[0062] From Table 2 and Figure 3 It can be seen that the sheet resistance can be adjusted by adjusting the Ag thickness in the metal electrode based on the Al pre-buried layer. Under the same thickness of the Al layer, the multilayer electrode with an 11nm Ag layer exhibits a lower sheet resistance value than the 9nm Ag layer, and a slightly higher sheet resistance than the 13nm Ag layer. However, as an electrode, the transmittance must also be considered, and the overall transmittance of the multilayer electrode is largely affected by the thickness of the intermediate Ag layer. Figure 4The transmittance of the semi-transparent multilayer electrodes prepared in Examples 1 to 3 shows that the multilayer electrode with an Ag layer of 11 nm exhibits a larger transmittance, and the single-junction perovskite solar cell prepared with a multilayer electrode with an Ag layer thickness of 11 nm as the top electrode has the best photoelectric performance, while in Example 1, the conductivity is affected due to the thin Ag layer, and in Example 3, the thicker Ag layer affects the transmittance, thereby affecting the overall performance of the device.
[0063] Example 4
[0064] The preparation method of the perovskite / crystalline silicon four-terminal stacked solar cell with a semi-transparent multilayer electrode in this embodiment is basically the same as that in Example 2, except that the thickness of the Al layer inserted before the growth of Ag is 2 nm.
[0065] Tables 3 and 4 are the square resistance values of the semi-transparent multilayer electrodes prepared in Example 2 and Example 4, respectively, and the performance parameters of single-junction perovskite solar cells with different thicknesses of Al layers. As shown in Table 3, compared with the metal electrode with a 1nm Al layer, the metal electrode with a 2nm Al layer has a square resistance increased from 15.7Ω / sq to 22.2 / sqΩ, and the transmittance is also reduced. This is because as the thickness of the Al layer increases, the Al islands begin to thicken and transform into three-dimensional islands, but the density of the Al islands does not increase. Since the Al islands have a stronger scattering effect on light and electrons, the transparency and conductivity of the multilayer electrode will decrease with the increase in the thickness of the Al layer. The performance parameters of single-junction perovskite solar cells with Al layers of different thicknesses are shown in Table 4. It can be seen that the best energy conversion efficiency is obtained when the thickness of Al is 1nm.
[0066] Table 3 Sheet resistance of semi-transparent multilayer electrodes with different thickness of Al layer
[0067] electrode D1 / Al(2nm) / Ag(11nm) / D2 D1 / Al(1nm) / Ag(11nm) / D2 Square resistance (Ω / sq) 22.2 15.7
[0068] Table 4 Performance parameters of single-junction perovskite solar cells with different thicknesses of Al layer
[0069] parameter Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) Efficiency(%) D1 / Al(2nm) / Ag(11nm) / D2 1.12 18.13 78.21 15.94 D1 / Al(1nm) / Ag(11nm) / D2 1.13 18.84 80.02 17.30
[0070] Example 5
[0071] The perovskite / crystalline silicon four-terminal stacked solar cell was prepared by the same method as in Example 2, except that the semi-transparent metal electrode layer was a multilayer structure formed by SnO2 / Al / Ag / SnO2, i.e., in step (6), after the C 60 After that, SnO2 / Al / Ag / SnO2 materials were deposited in sequence. The square resistance of the electrode was measured to be 15.7Ω / sq, and the transmittance reached 69.74%. The square resistance was low and the transmittance was good, which can be used to prepare high-performance stacked solar cells.
[0072] Comparative Example 1
[0073] The preparation method of a perovskite / crystalline silicon four-terminal stacked solar cell with a semi-transparent multilayer electrode is basically the same as that of Example 2, except that an Al layer is not evaporated between the LiF layer and the Ag layer.
[0074] As shown in Table 5, compared with the metal electrode without the Al layer inserted, the square resistance of the multilayer electrode with the transition metal Al as the pre-buried layer is reduced from 69.5Ω / sq to 15.7Ω / sq, which improves the conductivity of the multilayer electrode. This is because depositing a thin metal Al layer before depositing Ag can improve the morphology of the Ag metal film, reduce the permeation threshold of continuous film formation, and enhance the adhesion of the metal film to the substrate, thereby improving the conductivity of the multilayer electrode. It can also be seen from the photoelectric performance of the single-junction semi-transparent perovskite device prepared in Table 6 that the efficiency of the device with a layer of Al inserted in the metal electrode can reach 17.3%, indicating that the semi-transparent multilayer electrode and its perovskite / crystalline silicon four-terminal stacked solar cell prepared by the present invention are simple to operate, reduce costs, and significantly improve the photovoltaic performance of the device, and have a rare industrialization advantage.
[0075] Table 5 Square resistance of different metal electrodes
[0076] electrode D1 / Ag(11nm) / D2 D1 / Al(1nm) / Ag(11nm) / D2 Square resistance (Ω / sq) 69.5 15.7
[0077] Table 6 Photoelectric performance of different devices
[0078] parameter Voc(V) <![CDATA[Jsc(mA / cm) 2 ]]> FF(%) Efficiency(%) D1 / Ag(11nm) / D2 1.11 17.43 63.64 12.26 D1 / Al(1nm) / Ag(11nm) / D2 1.13 18.84 80.02 17.30
[0079] In summary, the invention obtains a semi-transparent multilayer electrode with high transmittance and low square resistance by sequentially evaporating dielectric / Al / Ag / dielectric. The perovskite / crystalline silicon four-terminal stacked solar cell prepared using the semi-transparent multilayer electrode has high energy conversion efficiency and reduces the preparation cost, which is suitable for large-area preparation and is conducive to the commercialization process.
[0080] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0081] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A perovskite / crystalline silicon four-terminal tandem solar cell, comprising a top cell and a bottom cell, characterized in that: The top cell is a perovskite solar cell, and the bottom cell is a crystalline silicon cell; the top cell includes a conductive substrate layer, a hole transport layer, a perovskite layer, an electron transport layer, a modification layer and a semi-transparent metal electrode layer stacked in sequence; the semi-transparent metal electrode layer is a multilayer structure formed by sequentially stacking medium 1 / Al / Ag / medium 2; both medium 1 and medium 2 are transparent materials.
2. The perovskite / crystalline silicon four-terminal tandem solar cell according to claim 1, characterized in that: The medium 1 is LiF or SnO2, and the medium 2 is MoO3 or SnO2.
3. The perovskite / crystalline silicon four-terminal tandem solar cell according to claim 1, characterized in that: In the semi-transparent metal electrode layer, the thickness of the Al layer is 1-2 nm, and the thickness of the Ag layer is 9-13 nm.
4. The method for preparing a perovskite / crystalline silicon four-terminal tandem solar cell according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Providing a conductive substrate; S2. Preparing a hole transport layer on the conductive substrate; S3. Preparing a perovskite layer on the hole transport layer; S4. Preparing an electron transport layer on the perovskite layer; S5. Vacuum evaporation of a modified layer on the electron transport layer; S6. Vacuum-depositing medium 1, Al, Ag and medium 2 on the modified layer in sequence to form a semi-transparent metal electrode layer to prepare a perovskite solar cell; S7. Cover the surface of the silicon cell with one side of the perovskite solar cell coated with a semi-transparent metal electrode layer to obtain the perovskite / crystalline silicon four-terminal stacked solar cell.
5. The method for preparing a perovskite / crystalline silicon four-terminal tandem solar cell according to claim 4, characterized in that: In step S2, the hole transport layer is P3CT, and the preparation steps are: spin coating P3CT on the surface of the conductive substrate, the spin coating conditions are 3900-4100 rpm for 30-40s, and annealing at 100-105°C for 9-11min after spin coating.
6. The method for preparing a perovskite / crystalline silicon four-terminal tandem solar cell according to claim 4, characterized in that: In step S3, the preparation method of the perovskite layer is: dissolving methylammonium iodide, methylammonium bromide and lead iodide in an ionic liquid at a molar ratio of 1: (1.5-1.53): (2.5-2.56) to obtain a precursor solution; using a heated spin coating technique to spin coat the precursor solution on the surface of the hole transport layer, and annealing to obtain the perovskite layer.
7. The method for preparing a perovskite / crystalline silicon four-terminal tandem solar cell according to claim 6, characterized in that: The substrate temperature of the heated spin coating technology is 50-100° C., the annealing temperature is 80-120° C., and the annealing time is 5-10 minutes.
8. The method for preparing a perovskite / crystalline silicon four-terminal tandem solar cell according to claim 4, characterized in that: The electron transport layer in step S4 is PCBM, and the preparation steps are: spin coating the PCBM solution on the perovskite layer, the spin coating conditions are 900-1100 rpm for 50-60s, and then spin coating at 1900-2100 rpm for 2-3s.
9. The method for preparing a perovskite / crystalline silicon four-terminal tandem solar cell according to claim 4, characterized in that: The modified layer in step S5 is C 60 , with a thickness of 17 to 22 nm.
10. Application of the perovskite / crystalline silicon four-terminal tandem solar cell according to any one of claims 1 to 3 in the field of optoelectronics.
Citation Information
Cited By
Four-end laminated solar cell based on ultra-wide-band-gap perovskite and preparation method of four-end laminated solar cell
CN120302811A
Perovskite / organic four-terminal laminated cell and preparation method thereof
CN120787032A
